1999
DOI: 10.1159/000016909
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver and Nonalcoholic Steatohepatitis. Where Do We Stand and Where Are We Going?

Abstract: Background: Fatty liver (FL) is the most common liver disease but its clinical significance remains elusive. Nonalcoholic steatohepatitis (NASH) is increasingly recognized as a cause of liver failure, sometimes recurring following transplantation. Recent data on both conditions are critically reviewed. Methods: A Medline search of the medical literature (1990 to September 1998) and cross-references was performed. Results: FL most commonly affects middle-aged men with obesity, altered glucose metabolism, hyperl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 63 publications
(98 reference statements)
1
23
0
Order By: Relevance
“…However, examples from the animal world have led to the speculation that they might represent an adaptive response to anticipated food shortage. 3,4 Therefore, HS has recently been proposed to represent the liver counterpart of the 'thrifty genotype' 5 but it may also herald ominous biological and clinical consequences in humans. Aim of the present reappraisal is to update relevant issues of HS and IR that have come to the light following the conference held in Den Haag in 2000.…”
Section: Does Hepatic Steatosis Serve Any Biological Purposes?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, examples from the animal world have led to the speculation that they might represent an adaptive response to anticipated food shortage. 3,4 Therefore, HS has recently been proposed to represent the liver counterpart of the 'thrifty genotype' 5 but it may also herald ominous biological and clinical consequences in humans. Aim of the present reappraisal is to update relevant issues of HS and IR that have come to the light following the conference held in Den Haag in 2000.…”
Section: Does Hepatic Steatosis Serve Any Biological Purposes?mentioning
confidence: 99%
“…3 However, the biological rationale for such 5% cut-off has recently been challenged. Indeed a Finnish study reported that 50% of 30 normal men had, on average, only 1.7 ± 0.2% of liver fat content as evaluated through proton spectroscopy.…”
Section: Is Hs a Normal Finding?mentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, a large body of evidence [8,38,39,51,52,61,[113][114][115][116] defi nitely supports the pathogenic role of IR in NAFLD and includes this condition within the boundaries of the MS.…”
Section: Evidence For Ir As the Key Pathogenic Factor In The Developmmentioning
confidence: 80%
“…The liver appears to be a target organ of a disease (the MS) which is systemic in nature and therefore carries implications for both hepatic and extrahepatic manifestations and complications [51,61] ( fi g. 1 ).…”
Section: Defi Nitions and Synonymsmentioning
confidence: 99%